A Study of Creativity of Students at Secondary Level in Reference to Their Socio-Economic Status and Type of Schools - Dr Pooja Bharti (INTERNATIONAL JOURNAL OF RESEARCH IN COMMERCE, IT, ENGINEERING AND SOCIAL SCIENCES ISSN: 2349-7793 Impact Factor: 6.876, 2008)
The aim of this study was to find out the creativity of students at secondary level in reference to their socio-economic status and type of schools. The survey method was used in this study. A total sample of 200 students at secondary level were selected by using the simple random technique.Sample was selected from CBSE (Central Board of Secondary Education) and UPBSE (Uttar Pradesh Board of Secondary Education) affiliated school of GhaziabadDistrict of Uttar Pradesh. The finding revealed that there is a significant difference in creativity of students at secondary level in reference to their socio-economic status and type of schools.